AN ANALYSIS OF FLOUTING MAXIM IN “THE B.F.G” MOVIE - Nur Ulfah, Rena Al Asyifa; Afrilia, Resti (IKIP Siliwangi, 2018)
This research studies about flouting maxim in The B.F.G movie. The research concerns on finding the flouting maxims in The B.F.G movie. This research employed mainly descriptive qualitative method to support in interpreting and analysing the data. The data of this research were utterances produced by Sophie and BFG as main characters in The B.F.G movie. The context of the research was the dialogues of the movie. The data sources of this research were The B.F.G and its script. Meanwhile, the primary instrument of this research was the researcher ourselves. The data were collected by downloading the movie and the script, watching the movie, and then collecting the data which reflects the phenomena of maxim flouting. The paper examines the use of flouts in different situations and explores in what situations the different characters flout the maxims for any conversation. The results show that there were 10 flouting maxims of quantity (42%); 10 flouting maxims of relevance (42%); 2 flouting maxims of quality (8%); and 2 flouting maxims of manner (8%). Hence the total number of flouting maxims is 24. These results suggest that the use of flouts has to do with their different personalities and communities.Keywords: Cooperative Principle, Grice’s Maxim, Flouting MaximHow to Cite: Ulfah-1, R.A.A.N.U.-1., Afrilia, R-2. (2018). An Analysis of Fluting Maxim in BFG Movie. Project, X (X), XX-XX. INTRODUCTIONCommunication is a medium to convey meaning from one to another. As stated by Yule (2006) that communication involves word recognition and meaning recognition. There could be hidden intention in some utterances. Failing to recognize those intentions may lead to misunderstanding and even a dispute. Nevertheless, listener is not always to be in guilt. Sometimes in communication, the speaker may provide incomplete or unclear utterance hence the listener found difficulties to comprehend. Thus it is claimed that language as a tool for communication serves as an instrument to maintain a good relationship between the speaker and the hearer. Dealing with language and communication, cooperative principle proposed by Grice serves as means to achieve effective communication. It is described that speakers and listeners must give contribution as required by each other so that both of them may come to the same understanding of the meaning they are trying to convey. Grice elaborates four conversational maxims: maxim of relevance, maxim of quantity, maxim of quality, and maxim of manner. During conversation, speakers may break the rule of the maxims. The flouting of the maxims may occur in daily life or in movies. Movies as one of literary works mostly functions to entertain the audience. The flouting maxims in movies may be intentionally created to achieve the purpose of entertaining. The BFG is one fantasy adventure film released in 2016 by Walt Disney. It tells about the journey of two different species, a human (Sophie) and a giant (that Sophie called Big Friendly Giant). Since they are from different group of communities, their communication may run ineffective. This study aims at analyzing the flouting maxims occurred in The BFG movie.The Cooperative Principle Cooperative Principle is the basic principle in pragmatics. The Cooperative Principle is principle of conversation that was proposed by Grice. He called The Cooperative Principle as when we try to talk to be cooperative by elevating. He says, “make your conversational contribution such as is required, at the stage at which it occurs, by the accepted purpose or direction of talk exchange in which you are engaged.” Within this principle, he intended four maxims.(Grundy, 1998) (in Ginarsih, 2014)Grice’s MaximMaxim of RelevanceMaxim of relation: This maxim may seem clear in the first look but as Grice himself mentioned it is very difficult to define it exactly: